2014
DOI: 10.1186/1471-2334-14-s1-s5
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis and HIV co-infection in children

Abstract: HIV is the top and tuberculosis is the second leading cause of death from infectious disease worldwide, with an estimated 8.7 million incident cases of tuberculosis and 2.5 million new HIV infections annually. The World Health Organization estimates that HIV prevalence among children with tuberculosis, in countries with moderate to high prevalence, ranges from 10 to 60%. The mechanisms promoting susceptibility of people with HIV to tuberculosis disease are incompletely understood, being likely caused by multif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
120
1
7

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(129 citation statements)
references
References 67 publications
1
120
1
7
Order By: Relevance
“…One of the key unanswered questions in the field of childhood TB concerns the nature of predisposition to the development of severe clinical forms in only a minority of infected children. HIV infection predisposes subjects to severe forms of childhood TB, but such infection is observed in only a small fraction of TB affected children . The last decade has provided a new clue to help us solve this riddle, by showing that at least some cases of severe TB, in HIV‐seronegative children, can be explained by single‐gene inborn errors of immunity .…”
Section: Introductionmentioning
confidence: 99%
“…One of the key unanswered questions in the field of childhood TB concerns the nature of predisposition to the development of severe clinical forms in only a minority of infected children. HIV infection predisposes subjects to severe forms of childhood TB, but such infection is observed in only a small fraction of TB affected children . The last decade has provided a new clue to help us solve this riddle, by showing that at least some cases of severe TB, in HIV‐seronegative children, can be explained by single‐gene inborn errors of immunity .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, TB is the leading cause of deaths by HIV-positive individuals as, in 2015, 1 in 3 HIV deceases was linked to TB infection. In the context of multidrug-resistance, approximately 480 000 people developed multidrug-resistant TB (MDR-TB) worldwide and the major causes are inappropriate treatment, misuse of drugs or use of poor quality medicines (Venturini et al, 2014; WHO, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…There are limited published studies directly evaluating the effect of rifampicin on immunologic and virologic outcomes in HIV-TB co-infected children on NVP based ART regimens and it is important to study this because unlike adults, children tend to have higher viral loads and are thus less likely to be adequately suppressed with lower plasma NVP drug levels. 18 Rifampicin is a known strong inducer of cytochrome P450 and as such results in reduced plasma concentrations of NNRTIs and PIs if used concurrently with these drugs. 19 Both adult and paediatric studies done in Africa, Thailand and India have shown varying levels of the effect on NVP plasma levels as a result of the drug-drug interaction during concomitant use of a rifampicin containing anti-TB regimen and a NVP based ART regimen.…”
Section: Discussionmentioning
confidence: 99%